Marriage-Immigrant Filipina Wives’ Acculturation and Learning Experiences in South Korea - Jihyun Kim (Adult Education Research Conference, 2014)
This paper discussed findings from a qualitative study based on interviews with 20 Filipinas who married a Korean husband and investigated their acculturation process of living in Korea. One strong theme presented in this paper was that marriage-immigrant women accepted the traditional oppressed position of daughter-in-law in traditional Korean patriarchy family model as genuine Korean culture.